Elastic flexibility tuning via interaction factor modulation in molecular crystals. Issue 65 (27th July 2018) - Mishra, Manish Kumar; Kadambi, Sourabh B.; Ramamurty, Upadrasta; Ghosh, Soumyajit
Abstract : We report the design of a series of nonhalogenated and halogenated molecular crystals with specific structural features, which are essential for pronounced elasticity. Abstract : We report the design of a series of nonhalogenated and halogenated molecular crystals with specific structural features, which are essential for pronounced elasticity. These features involve (a) isotropic weak and dispersive interactions, and (b) corrugated molecular packing with interlocked structures. The effects of intermolecular interactions on the elastic properties of the crystals are ascertained using nano-scale mechanical characterization methods.